The first South African species of Jeanneliusa Bernhauer, with remarks on diagnostic characters of Dorylomimini (Coleoptera, Staphylinidae: Aleocharinae) - Jałoszyński, Paweł (Zootaxa, 2025)
The first species of the Afrotropical Dorylomimini genus Jeanneliusa Bernhauer known to occur in the Republic of South Africa, J. kwazulua sp. nov. is described. Morphological characters included in diagnoses of Dorylomimini and Jeanneliusa are discussed.